Gravity in the Exchange Rate Factor Structure - Lustig, Hanno; Richmond, Robert J (Review of Financial Studies, 2020)
Abstract We relate the risk characteristics of currencies to measures of physical, cultural, and institutional distance. Currencies of countries which are more distant from other countries are more exposed to systematic currency risk. This is due to a gravity effect in the factor structure of exchange rates: When a currency appreciates against a basket of other currencies, its bilateral exchange rate appreciates more against currencies of distant countries. As a result, currencies of peripheral countries are more exposed to systematic variation than currencies of central countries. Trade network centrality best predicts a currency’s average exposure to systematic risk.